Factors Affecting the Quality of Sexual Life in Iranian Elderly Men With Andropause - Mojtaba Mohammadi; Hamid Allahverdipour; Akram Ghanbari Moghaddam; Hossein Matlabi (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives Andropause is the common term for menopause in older men, which is characterized by a decrease in testosterone levels. Many elderly men with andropause have difficulty or are embarrassed to talk about sexual topics, which causes a lack of information or wrong beliefs and attitudes towards this issue, especially among families. The existing studies in Iran have not had a deep and special attention on this issue. Therefore, this study aims to qualitatively investigate the factors affecting the quality of sexual life in Iranian elderly men with andropause.  Methods & Materials This is a qualitative study conducted in 2022 using the content analysis method. Using a purposeful sampling method, 14 elderly men with andropause were selected from among those who visited five health centers in different areas of Mashhad city in Iran. Data were collected using a semi-structured interview. Data analysis was done at the same time as sampling by using the conventional content analysis method. MAXQD software was used for data management.  Results The mean age of the participants was 70 years. Eight men had primary education, three had middle school education, one had a high school diploma, and two were illiterate. The findings included 290 codes, 19 subcategories, 9 categories, and 3 themes. The themes were perceived sexual impotence, non-sexual feelings and experiences, and the desire to have an active sexual life.  Conclusion The result of in-depth interviews with the elderly with andropause showed the components that can be addressed by officials and researchers for facilitating appropriate planning in this area. The knowledge of the existing situation and how the affecting factors can be the basis of new studioes in this field.